INTEGRASI NILAI FILOSOFIS BUDAYA LOKAL DALAM PENGEMBANGAN MODEL PEMBELAJARAN TARI UNTUK MENINGKATKAN APRESIASI SENI SISWA - Mahfud Tohari; Astuti, Fuji; Nerosti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The primary objective of this research is to analyze the incorporation of local philosophical principles into the creation of dance education frameworks aimed at elevating students' aesthetic awareness. Conventional dance instruction frequently prioritizes physical technique, often neglecting the intrinsic spiritual meanings of the art form. Utilizing a qualitative descriptive design centered on a literature review, this investigation synthesized data from various academic journals and policy reports published between 2020 and 2025. The results demonstrate that embedding local wisdom enables students to transition from mere mimicry to a profound comprehension of artistic intent. Consequently, the study suggests that reinforcing philosophical foundations in dance pedagogy is vital for sustaining cultural pertinence and spiritual integrity within modern education.